The Protection of Human Rights in the Mexican Republicanism - Aguilar Blancas, Carlos Alberto (The Age of Human Rights Journal, 2015)
Democracy is not only a procedure of choice and citizen participation, but also a set of values that affirm freedom and citizen’s rights. The reform of 2011 rose to constitutional rank the defence, protection and promotion of human rights, representing an unprecedented historic breakthrough. With these reforms, Mexico seeks to consolidate its constitutional system adapting it to reality, increasing its cultural diversity, values and traditions that have been shaping the Mexican identity. The full knowledge of their rights produces a citizenship aware of them, which, even for Mexico, is a long-term task.